Profitability Analysis of Price-Taking Strategy in Disequilibrium - Weihong Huang (Discrete Dynamics in Nature and Society)
Conventional economic assumption that more sophistication in decision making is better than less is challenged with a profitability analysis conducted with an oligopolistic model consisting of a naive firm and a group of sophisticated firms. While the naive firm is assumed to adopt a simple Cobweb strategy by equating its marginal cost of current production to the last period's price, the sophisticated firms can take either individually or collusively any conventional sophisticated strategy such as Cournot and Stackelberg strategies. Contrary to the economic intuition, it is not the sophisticated firms but the naive firm who triumphs in equilibrium as well as during the dynamical transitionary periods, no matter what strategies the sophisticated firms may take. Moreover, when the economy turns cyclic or chaotic, a combination of the Cobweb strategy with a cautious adjustment strategy could also bring relative higher average profits for the naive firm than its rivals.